Study of the Eco-Economic Indicators by Means of the New Version of the MERGE Integrated Model. Part 1 - Digas, Boris Vadimovich; Rozenberg, Valeriy Lvovich; Boyarskikh, Anastasiya Igorevna (Economy of Regions, 2015)
One of the most relevant issues of the day is the forecasting problem of climatic changes and mitigation of their consequences. The official point of view reflected in the Climate doctrine of the Russian Federation consists in the recognition of the need of the development of the state approach to the climatic problems and related issues on the basis of the comprehensive scientific analysis of ecological, economic and social factors. For this purpose, the integrated assessment models of interdisciplinary character are applied. Their functionality is characterized by the possibility of construction and testing of various dynamic scenarios of complex systems. The main purposes of the computing experiments described in the article are a review of the consequences of hypothetical participation of Russia in initiatives for greenhouse gas reduction as the Kyoto Protocol and approbation of one of the calculation methods of the green GDP representing the efficiency of environmental management in the modeling. To implement the given goals, the MERGE optimization model is used, its classical version is intended for the quantitative estimation of the application results of nature protection strategies. The components of the model are the economic-energetic module, climatic module and the damage assessment module. In the work, the main attention is paid to the adaptation of the MERGE model to a current state of the world economy in the conditions of a complicated geopolitical situation and introduction of a new component to the model, realizing a simplified method for calculation the green GDP. The Project of scenario conditions and the key macroeconomic forecast parameters of the socio-economic development of Russia for 2016 and the schedule date of 2017-2018 made by the Ministry of Economic Development of the Russian Federation are used as a basic source of entrance data for the analysis of possible trajectories of the economic development of Russia and the indicators of their ecological efficiency. Calculations show that Russia has reserves allowing its participation in the nature protection initiatives consisting in the non-exceedance of the emissions levels of 1990 by 2020-2025. At the same time, a goal of increasing the ecological efficiency of the Russian GDP is relevant and demands to address this matter urgently. We suppose that modeling results may be in demand by the competent bodies taking managerial decisions.